3D Printed Wrist Splint for Carpal Tunnel Syndrome in a Cigarette-Rolling Worker at RSUD Sumberglagah: A Case Study - Gatot Sunarto; Ellysa Okky Gusma; dea Septianiputri; Rahmat Apriyanto; Riska Permatasari (Journal of Prosthetics Orthotics and Science Technology, 2026)
Background: Carpal tunnel syndrome (CTS) is a prevalent entrapment neuropathy among manual workers performing repetitive wrist loading and sustained precision grip. Cigarette-rolling workers face elevated risk due to prolonged wrist flexion and repetitive pinch activity. Despite the efficacy of wrist orthoses, conventional devices often provide suboptimal anatomical conformity and restrict occupational hand function. Three-dimensional printing enables patient-specific fabrication at low cost, yet clinical evidence in occupational rehabilitation remains limited. Aims: This study evaluated the fabrication workflow and clinical outcomes of a customized 3D-printed CTS wrist splint in a cigarette-rolling worker, focusing on efficiency, anatomical fit, cost, and functional performance. Methods: A single-case study design was employed consistent with established methodology for novel clinical workflow documentation, to evaluate practicability rather than population-level efficacy. The participant was a 38-year-old female with mild-to-moderate right-hand CTS. A CAD-designed PLA+ orthosis was fabricated via FDM 3D printing and hot-water thermoforming. Primary outcomes wrist posture, pain, fatigue, endurance, and comfort were assessed at baseline, post-fitting, Day 7, and Day 14 via structured observation and KPOP Plus telemonitoring. Results: Digital fabrication required 384 minutes and 60.31 g of PLA+ at a material cost of IDR 16,200. Wrist posture improved to near-neutral alignment, while pain, fatigue, and endurance improved without skin complications. Telemonitoring confirmed sustained symptom relief and device comfort through Day 14. Conclusion: Digitally fabricated 3D-printed wrist orthoses were feasible, clinically beneficial, and cost-effective for occupational CTS management. This case demonstrates an integrated workflow combining CAD design, FDM printing, thermoforming, and telemonitoring. Keywords: Carpal tunnel syndrome; Digital fabrication; 3D printing; Wrist orthosis; Occupational health